Baby animals - Costamanga , Beatrice (Pheonix International Publications, Chicago, Illinois, 2020, 2020)
Lift-the-flap book with full color photographs of baby animals along side the words used to describe them such as Sea Turtle Hatchling, Hedgehog Hoglet, Elephant Calf
Scientific Notions
Keywords: Animals Infancy; Lift-the-flap books